Karting - Barrett, Norman S. (New York : F. Watts, 1988)
Color illustrations and text provide an introduction to the motor sport of karting.
Booklist.
5.3
3-5.
3-6
Keywords: Karting -- Juvenile literature; Karting; Karts and karting